2023
DOI: 10.3390/su15065445
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Care Attitudes and Intention to Purchase Green Products: Impact of Environmental Knowledge, Word of Mouth, and Green Marketing

Abstract: The intention to purchase green products cannot be separated from environmental consciousness among people. This study analyzes the effect of environmental knowledge, word of mouth (WOM), and green marketing on environmental care attitudes and the intention to purchase green products. A total of 159 valid questionnaires were analyzed with structural equation modeling. The empirical results indicate that environmental knowledge significantly affects environmental care attitudes. In addition, green marketing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Global trend in sustainability marketing goes beyond standard profit-driven techniques by stressing the three bottom lines: people, planet, and profit (Ahmed et al, 2022;Correia et al, 2023;Simanjuntak et al, 2023). Businesses that match their aims with broader social and environmental goals may build a favourable brand image, increase consumer loyalty, and promote long-term profitability.…”
Section: Results and Discussion Global Sustainable Marketing As A Trendmentioning
confidence: 99%
“…Global trend in sustainability marketing goes beyond standard profit-driven techniques by stressing the three bottom lines: people, planet, and profit (Ahmed et al, 2022;Correia et al, 2023;Simanjuntak et al, 2023). Businesses that match their aims with broader social and environmental goals may build a favourable brand image, increase consumer loyalty, and promote long-term profitability.…”
Section: Results and Discussion Global Sustainable Marketing As A Trendmentioning
confidence: 99%
“…Many consumers are concerned about the environment due to environmental degradation and the rise of harmful activities (Aseri & Ansari, 2023). Those who know and are aware of environmental issues will research the environmental impact of products before purchasing (Simanjuntak, Nafila, Yuliati, Johan, Najib, & Sabri, 2023). Earlier studies (Kinnear, Taylor, & Ahmed, 1974) evaluated the EC in relation to the PCE as a part of personality (Apaydin & Szczepaniak, 2017;Kinnear et al, 1974).…”
Section: Environmental Concern (Ec)mentioning
confidence: 99%
“…This indicated that although the impact value of EC on GPI remained modest, it still portrayed a shift in the Indonesian consumers' GPI from non-sustainable to sustainable packaging for environmental protection purposes. The growing number of people concerned about the environment increased the GPI for the environmentally friendly products (Simanjuntak et al, 2023). In addition, the development of a market for green product packaging suggested that the consumer awareness of the environment was rising above the surface.…”
mentioning
confidence: 99%
“…After all, they prefer to link them with higher quality and better brand image. In addition, a study discovered that consumers will pay a higher price if they care about the environment [23]. H1.…”
Section: Green Price and Consumer Buying Behaviormentioning
confidence: 99%